Il ritorno della Storia. Note su Dora Bruder, Jan Karski, Les Bienveillantes (ENTHYMEMA, 2020)
The trial of the realist novel that began in the late nineteenth and early twentieth centuries in France until 1960 claimed the reduction and the elimination of history from the aesthetic project of a part of literature. In the eighties and nineties, with the collapse of ideologies, the postmodern novel reintroduce the historical dimension. Three examples, Modiano, Haenel, Littel, shows the great return of History in the novel with characters that crosses darker and more terrible sides of human condition.